Injuries in elite athletes - Nikola Radulović; Ilona Mihajlović; Milan Šolaja; Ratko Pavlović (University of Novi Sad, Faculty of Sport and Physical Education, 2019)
The purpose of this research was to review current research findings related to injuries in elite athletes. For the needs of the paper, professional and scientific literature was analyzed from prestigious scientific journals. The types of athletic injuries that occur are dependent on the athletic discipline. The most commonly injured sites in athletes are the front and back muscles of the thigh and in the ankle joint. The results of this study have indicated that the causes of most injuries are due to overstraining and overload syndrome. These causes often arise from training procedures that have been implemented inadequately and usually relate to the volume and intensity of training without the application of injury prevention techniques.